2015
DOI: 10.1136/archdischild-2014-307590
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral haemorrhage in preterm neonates: does cerebral regional oxygen saturation during the immediate transition matter?

Abstract: The neonates of the IVH group showed significantly lower crSO2 values during the immediate transition, although there was no difference concerning SpO2 and HR. The additional monitoring of crSO2 during the immediate transition could reveal neonates with higher risk of developing an IVH later in the course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 33 publications
4
47
0
Order By: Relevance
“…We can only speculate that the different algorithms calculating values from measured changes in light absorption might be responsible for these differences. Taking this correlation into account, the present centiles are consistent with the crSO 2 centiles published by Pichler and colleagues [6]. In the present study, the 50th centile of cTOI at 2 min was higher compared to the 50th centile of crSO 2 [6], and remained higher until minute 5.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We can only speculate that the different algorithms calculating values from measured changes in light absorption might be responsible for these differences. Taking this correlation into account, the present centiles are consistent with the crSO 2 centiles published by Pichler and colleagues [6]. In the present study, the 50th centile of cTOI at 2 min was higher compared to the 50th centile of crSO 2 [6], and remained higher until minute 5.…”
Section: Discussionsupporting
confidence: 81%
“…These crSO 2 and cFTOE reference ranges were defined using the neonatal sensor of INVOS 5100C cerebral/somatic oximeter (Covidien, Boulder, Colo., USA). Two observational studies have reported on preterm infants with low crSO 2 values during the immediate transition that subsequently developed intraventricular haemorrhage [3,6]. A recent comparison of INVOS and NIRO 200NX (NIRO, Hamamatsu, Japan), both widely used NIRS devices in neonates, reported that crSO 2 values measured with INVOS are about 10% higher compared to the cerebral tissue oxygenation index (cTOI), which was measured with the NIRO 200NX [7].…”
Section: Introductionmentioning
confidence: 99%
“…21 Perhaps more significantly, lower levels of cerebral oxygenation have been associated with poor brain outcomes. [22][23][24][25][26] Future work should use a predefined strategy for data analysis, e.g., drawing a receiver-operating curve for the prediction of severe brain injury for varying levels of cerebral hypoxic burden. This could help the construction of the rationale for one rather than another threshold for intervention.…”
Section: Safe Ranges Based On Association With Brain Injurymentioning
confidence: 99%
“…Although pulse oximetry and electrocardiogram enable monitoring of heart rate continuously, they do not provide information about potentially compromised cardiocirculatory status influencing oxygen transport to tissue. Besides cardiocirculatory monitoring, there is growing interest to monitor the brain during this vulnerable phase, as the brain is sensitive to hypoxia-ischemia and its damage can result in poor short- and long-term neurological outcome [8]. …”
Section: Introductionmentioning
confidence: 99%